2017
DOI: 10.1177/0020715217722039
|View full text |Cite
|
Sign up to set email alerts
|

Host or hostile? Attitudes towards asylum seekers in Israel and in Denmark

Abstract: In this study, we focus on attitudes towards asylum seekers in two countries: Denmark and Israel. Both serve as interesting cases through which to study public sentiment of host populations for people seeking refuge. We examine the role of three core dimensions that have been relatively overlooked in previous studies: social contact with asylum seekers, the role of support for humanitarian policies and perceptions of legitimacy of the asylum seekers' claims. We also gauge the way perceptions of threat mediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 69 publications
1
28
0
1
Order By: Relevance
“…to asylum seekers, and to do so in relation to feelings of sympathy and perceived societal contribution, in addition to the much-researched role of perceived threat (Schweitzer et al 2005;Louis et al 2007;Hercowitz-Amir Raijman, and Davidov 2017;von Hermanni and Neumann 2019). Moreover, in contrast to previous research on helping intentions (Rudolph et al 2004), we focused on self-reported humanitarian behavior.…”
Section: Discussionmentioning
confidence: 99%
“…to asylum seekers, and to do so in relation to feelings of sympathy and perceived societal contribution, in addition to the much-researched role of perceived threat (Schweitzer et al 2005;Louis et al 2007;Hercowitz-Amir Raijman, and Davidov 2017;von Hermanni and Neumann 2019). Moreover, in contrast to previous research on helping intentions (Rudolph et al 2004), we focused on self-reported humanitarian behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the disparities and exclusion that existed in society prior to the Covid-19 pandemic intensified as a result of the virus, with the weaker parts of the population hardest hit. Worldwide, and in Israel in particular, asylum seekers comprise one of the most weakened groups in society ( Canetti et al 2016 ; Hercowitz-Amir et al 2017 ; Hochman 2015 ; Kalir 2015 ; Tirosh and Schejter 2017 ; Yacobi 2011 ). As such, it stands to reason that asylum seekers would be one of the hardest hit groups in society as a result of the Covid-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research to understand why the idea of immigration evokes strong negative reactions in some individuals but not in others has a long tradition in the social sciences (Hainmueller & Hopkins ). As for the Nordic countries, this research has brought valuable knowledge about how anti‐immigration ideas resonate in these populations (Knudsen ; Kestilä ; Ervasti et al ), including how people conceive of specific immigrant categories such as Muslims (Bevelander & Otterbeck ), Russian immigrants (Brylka et al ) or asylum seekers (Hercowitz‐Amir et al ). The focus, however, has mainly been the degree of immigration opposition rather than the character of peoples' attitudes.…”
Section: Introductionmentioning
confidence: 99%